Development of Anastrepha grandis (Diptera: Tephritidae) under constant temperatures and field validation of a laboratory model for temperature requirements. (October 2017) - Bolzan, Anderson; Nava, Dori E.; Smaniotto, Giovani; Valgas, Ricardo A.; Garcia, Flávio R.M.
Abstract: Anastrepha grandis (Macquart) is one of the main pests of cucurbits in the countries of Central and South America. Besides direct damage caused to fruits, A. grandis occurrence in producing regions can lead to export embargos. Despite its economic importance, little is known of the effects of temperature on its biology. This study investigated the development of A. grandis under different temperatures to estimate thermal requirements and then validated the model developed in the field. Development time was inversely proportional to temperature and greater fecundity and fertility were observed at 25 °C. Greater egg and pupa viabilities as well as a greater number of insects per fruit were also observed at 25 °C. The thermal threshold and the thermal constant for egg and pupal stages were 8.3 °C for both stages and 132.3 degree-days (DD) for the egg stage and 347.0 DD for the pupal stage. For the egg-to-adult period the values were 5.2 °C and 858.7 DD. Data collected in the field showed DD (937.9) and duration (79.7 d) values of the egg-to-adult period similar to those estimated in the laboratory. This information could support management of A. grandis, since the model for temperature requirements can be used to predict pest occurrence in crops and estimate the number of generations per year. Highlights: The relationship between thermal conditions and A. grandis development was observed. The work provides benefits for pest management in different regions and ecosystems. The thermal requirements of A. grandis were established.